On the design of a dual-band base station wire antenna. - Zaharis, Z. (IEEE Antennas & propagation magazine.)
A dual-band base station wire-antenna design is presented. The MoM and the simulated-annealing technique, for optimizing the antenna geometry, are used. The procedure starts from the design of a primary radiator, consisting of a dielectric covered driven dipole and a parasitic element. A Chebyshev antenna array is checked in both the 900 and 1800 MHz frequency bands, with and without the appropriate feed network. All the electrical characteristics, as well as the patterns of the antenna, are presented.